The Teaching Of Ethics And Its Implementation In Balinese Adolescents Life - Ni Ketut Kantriani (Jayapangus Press, 2020)
By nature, besides humans as individual beings, humans also social beings who have their own culture. Culture arises in humans because of the reason and mind in humans themselves. Humans can live perfectly if they live together with other humans, concerning other humans, certain norms or rules are required. The teachings of ethics motivate human life because through this, humans can build good relationships between humans and each other in harmony. The implementation of ethics can be found in societies in the world, both in advanced societies and societies with simple civilizations. In social life, everyone should behave well, thus they can create happiness for themselves and society. Therefore, in Hinduism, there is a basic ethics teaching that can bring humans to achieve harmony in social manners in society. The basis of ethical teachings is contained in the Vedic scriptures, one of which is Tri Kaya Parisudha. The teachings of ethics are important as a social guide in adolescents’ life in Bali.